2014
DOI: 10.1590/s0102-79722014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Procura-PALavras (P-Pal): uma nova medida de frequência lexical do português europeu contemporâneo

Abstract: ResumoNeste trabalho apresentamos as estratégias e os procedimentos adoptados na constituição de uma nova medida de frequência lexical do Português Europeu contemporâneo, o Procura-PALavras (P--PAL). Baseado num corpus de mais de 227 milhões de palavras, o P-PAL é uma aplicação web que oferece, por defeito, valores de frequência lexical para todas as suas entradas lexicais (lemas e formas) e que permite a computação de uma grande diversidade de outras medidas objectivas (lexicais e sublexicais) e subjectivas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…The sentences in each emotional category were matched for length (mean number of words and mean number of letters within words in the sentence) and per-million word frequency, considering the part of speech (PoS) of each word in the sentence, obtained from the Procura-PALavras lexical database (P-PAL; Soares et al, 2014, available at http://p-pal.di. uminho.pt/tools).…”
Section: Methodsmentioning
confidence: 99%
“…The sentences in each emotional category were matched for length (mean number of words and mean number of letters within words in the sentence) and per-million word frequency, considering the part of speech (PoS) of each word in the sentence, obtained from the Procura-PALavras lexical database (P-PAL; Soares et al, 2014, available at http://p-pal.di. uminho.pt/tools).…”
Section: Methodsmentioning
confidence: 99%
“…The EP words from the three conditions (O-P+, O-P-, O+P+) were also matched in logarithm frequency, biphone frequency, contextual diversity, length, and orthographic neighbors (all ps > .39) (see Table 2). The values of logarithm word frequency and contextual diversity for EP words were taken from ESCOLEX (Soares et al, 2014; an EP grade-level lexical database that gives numerous word frequency statistics for 1st to 6th grade children [6to 11-year-olds] computed from elementary textbooks) and the values of biphone frequency and length were retrieved from P-PAL (Soares et al, 2015; an EP lexical database that gives numerous word frequency statistics and the computation of several other lexical and sublexical objective and subjective metrics for adults).…”
Section: <Insert Here the Table 1>mentioning
confidence: 99%
“…In recent decades, the way in which different languages are represented and processed in the bilingual memory has been studied extensively (e.g., Comesaña, Perea, Piñeiro, & Fraga, 2009;Comesaña et al, 2015;Dijkstra el al., 2010;Kroll, Van Hell, Tokowicz & Green, 2010;Van Heuven & Dijkstra, 2010). Most of these studies have shown a simultaneous activation of words from both languages, that is, a non-selective language activation due to the existence of a common representation for both languages, at least at some level (Dijkstra et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each Basque word was paired with three EP words: (i) a correct translation (e.g., zuhaitz [tree] -árvore [tree]), (ii) a semantically related word (e.g., zuhaitz [tree] -folhas [leaves]), and (iii) an unrelated word (e.g., zuhaitz [tree] -faixas [sashes]; see Appendix A). Semantically related words were selected from the EP word association database for children (Comesaña, Fraga, Moreira, Frade, & Soares, 2014) whereas unrelated words were taken from the Procura-PALavras lexical database (P-PAL; Soares et al, 2014). Related and unrelated words were matched in length (5.8 and 5.9, respectively, p = .67), frequency per million (67.7 and 65.2, respectively, p = .87), number of orthographic neighbours (4.3 and 4.6, respectively, p = .72) and phonological neighbours (5.1 and 4.5, respectively, p = .54), as well as in grammatical category (note that most of the selected words were nouns [85%]).…”
Section: Stimulimentioning
confidence: 99%